Pelatihan Passing dan Shooting pada Permainan Sepak Bola Anak-anak - Zen Ali (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
Passing and shooting are two distinct techniques in football. There are six basic techniques in football: dribbling, controlling, passing, shooting, heading, and tackling. A football player must master all six basic techniques, including passing and shooting. Observations have revealed issues in the community of Pandan Wangi Village, Jerowaru Subdistrict, East Lombok Regency, such as the irony of many children in Pandan Wangi Village who enjoy playing football but lack a platform to develop their talents and potential. The objectives of this training are: 1) to enhance children's technical skills in performing passing and shooting in football; 2) to introduce the basic concepts of football to children, including proper techniques for passing and shooting; and 3) to serve as an effort to develop football potential and talent at the village level, and to generate interest in sports within the local community. The methods used in this activity include demonstration and explanation, repeated practice, and small-sided games. The results of this activity show an increased interest among participants, as evidenced by growing enthusiasm from the start to the end of the passing and shooting training program for children. The passing and shooting training in football for children in Pandan Wangi Village, Jerowaru Subdistrict, East Lombok Regency, is an important activity for developing the skills and physical and technical abilities of young participants. Football not only becomes a popular sport among children but also brings significant benefits in terms of character development and teamwork.